L’emploi antique des géomatériaux à Reims/Durocortorum - Gilles Fronteau; Sébastien Laratte; Alain Devos; Claire Pichard (Gallia)
Research carried out over the last twenty years on local geomaterials in the Reims region, as well as an important collection of Antiquity period archaeological corpuses, currently make it possible to identify the main characteristics of geomaterial supply and use in the Gallo-Roman city of Reims/Durocortorum. The establishment of the town during the late Iron Age (La Tène D), within the chalky plain, not far from the Île-de-France cuesta, strongly shaped future strategies for stone supply. Until the end of the early Roman Empire period, the densification and growth of the urban fabric only served to increase the need for building materials. And, in this area, fundamentally marked by the absence of quality dimension stone in the immediate vicinity of the city, in addition to imports, on the one hand this led builders to turn to soft, local materials, and on the other hand to search for replacements. Thus, the supply of building materials highlights the implementation of multiple strategies, including specific “regional” or extra-regional supplies, but also the optimization of the use of local resources. In this article, we propose to review the geomaterial resources identified in the ancient town of Durocortorum, according to their uses and availability in growing areas, starting from the city center and spreading to areas where investment in material supply was important. This analysis is illustrated by the ways in which these resources have been implemented, depending on context of construction or usage. Indeed, our observations demonstrate that each particular context of use had a specific range of geomaterials associated with it. The chalk on which the city is built is abundantly available, but is also a friable material, from which it is difficult to extract consistent blocks. If its use is widespread, from the stabilization of soils and roads, to its use in small rubble for certain protected spaces (cellars), the high alterability of the material likely did not allow its conservation in all examples of its use. In addition, its modest geotechnical qualities exclude it from use in construction of large complexes, which therefore would have required the importation of other materials. The construction of common facilities, such as residential buildings (mainly urban), or private utility buildings, is characterized by the use of local origin materials or materials extracted directly on site. These would have included: rubble stones, silt intended for the manufacture of adobe bricks, and of course chalk, in all of its various forms. Adobe bricks, locally referred to as earthen tiles, are raw earthen bricks, wherein chalk fragments are bound together with brown silt. Rubble stone of local origin (gritstone, sandstone) are most commonly seen in use for the lower parts of buildings (wall plates, bahut walls). On the other hand, the use of ornamental stones for luxurious residences necessitated the implementation of imported marble from outside the region. Rural peri-urban buildings exhibit almost exclusive use of perishable materials, such as cob and mud bricks or mud tiles, but also relatively abundant use of stone for tools, material goods or larger architectural elements. The utilitarian architectural programs, or those dedicated to the day-to-day life of the city and its surroundings, are marked by a selection of materials requiring specific qualities: relative to water for the aqueduct, or their resistance to the underground environment for the cryptoportici bases. Finally, the construction of monumental adornment for the ancient city, as well as adjacent funerary areas, led to the massive importation of materials from quarries located 30 to 45 km away. The Mars Gate example illustrates this use of large blocks of Lutetian limestone, sourced from a distant area in the region. Thus, the use of geomaterials can be understood as responding just as much to a logic of availability or accessibility, as to a capacity for implementation or requirements in terms of quality, as illustrated by the use of stones with low capillary action in foundations or stem-walls. In Reims, these different requirements required the importation of materials from sources located at a variable distance from the city.